Enhancing Employee Attendance Systems Through Integrated Monitoring And Automation - Yulianto, Tomi (PT Inovasi Pratama Internasional, 2025)
This study introduces a hybrid Employee Attendance System that integrates facial recognition with behavioral analytics for predictive absenteeism tracking. Through a pilot study in three multinational organizations, the system demonstrated a 25% improvement in attendance accuracy and a 40% reduction in manual HR interventions. The framework prioritizes data privacy through blockchain-enabled anonymization, ensuring compliance with global privacy laws. With advanced AI capabilities and cross-cultural adaptability, this system redefines attendance monitoring as a driver of organizational efficiency and employee satisfaction